2SPD-014 Cost study: reusable flexible ureteroscopes versus single-use in a healthcare facility. Issue 1 (23rd March 2023) - Dufossé, M; Martel, F; Benard, L; Petit, A
Abstract : Background and Importance: In our hospital, we use flexible ureteroscopes for lithiasis treatment, which is at high risk of material breakage. In the devices park, we have six adult devices (inadequate in view of the activity) and one paediatric (obsolete), which are often unavailable, for disinfection or repair. Aim and Objectives: To compensate for unavailability, we could use single-use devices. Our objective is to compare reusable versus single-use devices' costs, to determine if referencing single-use devices is relevant. Material and Methods: We set a working group, including urologists, pharmacists, biomedical engineers and health executive from disinfecting centre. We base the calculation of the cost on 300 uses per year. Reusable cost gather the purchase price, the amortisation expense for a 3 year product lifetime, disinfections cost (products, equipment, staff), maintenance contract and repair cost. Single-use cost is assimilated with the purchase price of 300 units. The manufacturer provides the console free of charge. Our study does not consider waste treatment cost. Results: For 300 uses, reusable ureteroscopes cost €133 360 yearly pre-tax (€445/unit): €27 813 for amortisation expense, €66 000 for maintenance contract, €20 594 for the repairs. Disinfection costs €12 900 yearly, in addition to €4 353 yearly for maintenance and €1700 for amortisation of equipment. If we only used single-use ureteroscopes, it would cost €184 500 yearly (€615/unit). The incremental cost would be €51 140 yearly. Conclusion and Relevance: Our results show that, in our case, single-use is more expensive, especially since we have a new disinfection facility for our reusable ureteroscopes. Moreover, the single-use ureteroscopes' picture quality is lower, which led the group to speak in favour of the park increase to eight units for usual use. In addition, it recommends punctual purchase of single-use in cases of unavailability or act at high risk of material breakage. Indications for paediatric use are rare, the group recommends purchasing a few single-use units and to write off the reusable ureteroscope. References and/or Acknowledgements: Conflict of Interest: No conflict of interest